1986
DOI: 10.1111/j.1365-2133.1986.tb02822.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold urticaria and virus infections: a clinical and serological study in 39 patients

Abstract: Thirty-nine patients with cold urticaria seen over a 12-year-period were re-examined. All but 12 still had positive skin tests for cold and only five of these had shown a spontaneous cure. Fourteen patients were prone to collapse on cold exposure. The incidence of atopy in this group was comparable to that in control groups. Cold urticaria is an extremely chronic disease. The mean disease duration was 9.3 years. Serum antibodies to Epstein-Barr virus, measles virus, cytomegalovirus (CMV), varicella-zoster viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
6

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
1
24
1
6
Order By: Relevance
“…Most studies in the literature showed a prevalence of atopic disorders in patients with cold urticaria that is similar to the general population (ϳ20%). 3,4,12 Moreover, in vivo and in vitro studies suggested a different pathophysiology of cold urticaria than asthma, allergic rhinitis, or eczema. One study did find a high rate of atopy among patients with cold urticaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies in the literature showed a prevalence of atopic disorders in patients with cold urticaria that is similar to the general population (ϳ20%). 3,4,12 Moreover, in vivo and in vitro studies suggested a different pathophysiology of cold urticaria than asthma, allergic rhinitis, or eczema. One study did find a high rate of atopy among patients with cold urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies report immersion for various time intervals (5-15 minutes) in different water temperatures (4 -15°C). 7,12 Caution must be taken when performing such a test. There are case reports of systemic reactions precipitated by this test, especially in very sensitive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Soğuk ürtikerli olgularda atopi sıklığı incelendiğinde, bazı çalışmalarda atopi sıklığı genel popülasyonla benzer bulunurken (8), bazı çalışmalarda ise daha yüksek oranlar bildirilmiştir (15,22,23). Bu çalışmada, soğuk ürtikerli hastalarda genel inhalan panel ile deri prik testleri sonuçlarına göre atopi sıklığı %48 olarak saptandı.…”
Section: Discussionunclassified
“…Hastaların %22-50'sinde atopi bildirilmiştir (4,5) ve yaklaşık 1/4'ünde diğer ürtiker formları (kolinerjik ürtiker, kronik idyopatik ürtiker, semptomatik dermografizm gibi) eşlik etmektedir (6). Bazı olgu sunumlarında, arı sokması, çeşitli enfeksiyonlar, infeksiyöz mononükleoz, Helicobacter pylori kolonizasyonu ve aşılama soğuk ürtikeri ile ilişkilendirilmiştir (4,(7)(8)(9). Ülkemizde Raynaud fenomeni olan hastalarda yapılan bir çalışmada %4.1 oranında soğuk ürtikeri bildirilmiştir (10).…”
Section: Gi̇ri̇ş Ve Amaçunclassified
“…Algunas infecciones virales (por ejemplo, la mononucleosis, la infección por VIH) (23)(24)(25), infecciones bacterianas (borreliosis) e, incluso, por parásitos (Helicobacter pylori, toxoplasma) (26,27) se han implicado como desencadenantes de la urticaria por frío.…”
Section: Exámenes De Laboratorio Pacienteunclassified